2021
DOI: 10.5334/pb.1059
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceived Impact of the Societal Lockdown of COVID-19 on Family Well-Being and on the Emotional and Behavioral State of Walloon Belgian Children Aged 4 to 13 Years: An Exploratory Study

Abstract: This exploratory study assessed parents’ perceptions of the emotional and behavioral impacts of the COVID-19 lockdown on their children. The total sample included 749 children, aged 4 to 13 years old (353 girls, 396 boys); 524 parents took part. The emotional and behavioral changes observed during the societal lockdown, family coexistence, the impact of COVID-19 on family well-being, and the frequency of social contacts before and during this lockdown were investigated. Results show that the most frequently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Fourth, information on children lacks precision since participants did not have to indicate the number of children, their age, if they were still living in the same house, if they had to accompany learning activities at home. Yet, these different elements have been proven to influence one’s well-being since the pandemic (e.g., Stassart, Wagener, & Etienne, 2021 ).…”
Section: Limitationsmentioning
confidence: 99%
“…Fourth, information on children lacks precision since participants did not have to indicate the number of children, their age, if they were still living in the same house, if they had to accompany learning activities at home. Yet, these different elements have been proven to influence one’s well-being since the pandemic (e.g., Stassart, Wagener, & Etienne, 2021 ).…”
Section: Limitationsmentioning
confidence: 99%
“…On the other hand, the psychological literature routinely studies children’s psychological well-being through their parents’ perceptions. This has been also done during the COVID-19 lockdown, for instance by Pisano et al ( 2020 ), Orgilés et al ( 2020 ), and Stassart et al ( 2021 ). For all these reasons, identifying those children who, according to their parents, have suffered more during the lockdown, might help policymakers to target interventions aimed at containing the surge of educational inequality.…”
Section: Introductionmentioning
confidence: 97%
“… 18 Again, one could doubt that parental perception of children emotional status may be affected by measurement error. However, the psychological literature has routinely used parental perceptions to study children’s psychological wellbeing, even during the lockdown (Orgilés et al, 2020 ; Pisano et al, 2020 ; Stassart et al, 2021 ). …”
mentioning
confidence: 99%
“…Such stressors can, in turn, influence the quality of family relationships, making patient and empathic parenting challenging at times (Osborne et al, 2008). Families in several European countries (Italy, Spain, and Belgium;Orgilés et al, 2020;Stassart et al, 2021) and the United Kingdom (Morgül et al, 2020) reported difficulties with family co-existence during the home confinement. In the United Kingdom, families who found co-existence difficult were more likely to report that their children's behavior and emotional state had changed for the worse since the lockdown had started (Morgül et al, 2020).…”
Section: Introductionmentioning
confidence: 99%